Get insightful responses to your questions quickly and easily on IDNLearn.com. Join our community to receive prompt and reliable responses to your questions from experienced professionals.
Sagot :
To solve the equation [tex]\( 4x - c = k \)[/tex] for [tex]\( x \)[/tex]:
1. Isolate the term involving [tex]\( x \)[/tex]:
Start with:
[tex]\[ 4x - c = k \][/tex]
Add [tex]\( c \)[/tex] to both sides to move the constant term to the right-hand side:
[tex]\[ 4x - c + c = k + c \][/tex]
Simplify:
[tex]\[ 4x = k + c \][/tex]
2. Solve for [tex]\( x \)[/tex]:
Now, divide both sides of the equation by 4 to isolate [tex]\( x \)[/tex]:
[tex]\[ x = \frac{k + c}{4} \][/tex]
Therefore, the solution for [tex]\( x \)[/tex] is:
[tex]\[ x = \frac{k + c}{4} \][/tex]
So, the correct answer is:
D. [tex]\( x = \frac{k + c}{4} \)[/tex]
1. Isolate the term involving [tex]\( x \)[/tex]:
Start with:
[tex]\[ 4x - c = k \][/tex]
Add [tex]\( c \)[/tex] to both sides to move the constant term to the right-hand side:
[tex]\[ 4x - c + c = k + c \][/tex]
Simplify:
[tex]\[ 4x = k + c \][/tex]
2. Solve for [tex]\( x \)[/tex]:
Now, divide both sides of the equation by 4 to isolate [tex]\( x \)[/tex]:
[tex]\[ x = \frac{k + c}{4} \][/tex]
Therefore, the solution for [tex]\( x \)[/tex] is:
[tex]\[ x = \frac{k + c}{4} \][/tex]
So, the correct answer is:
D. [tex]\( x = \frac{k + c}{4} \)[/tex]
We value your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. IDNLearn.com is your go-to source for dependable answers. Thank you for visiting, and we hope to assist you again.